PERBANDINGAN HASIL BELAJAR DAN KUALITAS KOLABORASI SISWA ANTARA KELOMPOK KECIL DAN KELOMPOK BESAR DALAM PEMBELAJARAN MENGGUNAKAN METODE EKSPERIMEN - Nuraini, Siti; Suseno, Nyoto; Riswanto, Riswanto; Harjati, Purwiro (Universitas Muhammadiyah Metro, 2021)
Abstract: The purpose of this research is to know the comparison of learningoutcomes and student collaboration quality between small group and largegroup in learning using experimental method,which learning outcomes arebetter between large groups and small groups, and which collaboration isbetter between large groups and small groups. Type of this research iscomparative with Posttest Only Control Group Design. Sampling is usingCluster Random Sampling. This study uses two classes, class X IPA 1 as asmall group with the number of students 33 students and class X IPA 2 as alarge group with the number of students 36 students. Data analysis this studyis using Chi-Square Test. The results showed that the difference of averageresult of study from small group was batter big group, it can be seen thattobserved 3,78 > ttable 2,00. Then, the average of collaboration quality of smallgroup was batter small group then big group, it can be seen that tobserved 2,73was > ttable 1,78. Suggestions submitted so that students' physics learningobtained optimal outcomes, it is advisable to apply experimental of smallgroup.Keywords: Result of study, collaboration, big group, small group, experiment